2016
DOI: 10.1038/srep30377
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease H1-dependent hepatotoxicity caused by locked nucleic acid-modified gapmer antisense oligonucleotides

Abstract: Gapmer antisense oligonucleotides cleave target RNA effectively in vivo, and is considered as promising therapeutics. Especially, gapmers modified with locked nucleic acid (LNA) shows potent knockdown activity; however, they also cause hepatotoxic side effects. For developing safe and effective gapmer drugs, a deeper understanding of the mechanisms of hepatotoxicity is required. Here, we investigated the cause of hepatotoxicity derived from LNA-modified gapmers. Chemical modification of gapmer’s gap region com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 51 publications
3
80
0
Order By: Relevance
“…Gapmer ASOs bind not just to mRNA, but also to pre‐mRNA introns to cleave and degrade pre‐mRNA (Kamola et al, ; Kasuya et al, ). Thus, when searching for off‐target candidate genes of gapmer ASOs, an in silico analysis of a database that fully includes human pre‐mRNA should be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Gapmer ASOs bind not just to mRNA, but also to pre‐mRNA introns to cleave and degrade pre‐mRNA (Kamola et al, ; Kasuya et al, ). Thus, when searching for off‐target candidate genes of gapmer ASOs, an in silico analysis of a database that fully includes human pre‐mRNA should be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of toxicity seems to apply equally to LNA and cEt, despite previous reports to the contrary, and is sequence-dependent. In the past year, three groups independently demonstrated that LNA and cEt gapmer ASOs induce liver toxicity by directing off-target RNase H cleavage of mismatched transcripts, particularly within introns 42-44 . Armed with this information, computational methods can be used to select ASOs with minimal complementarity to off-target transcripts (including introns).…”
Section: Chemical Evolution Of Asosmentioning
confidence: 99%
“…GapmeR molecules, causes RNaseH-mediated gene silencing, independent of RNA-Induced Silencing Complex (RISC), and therefore, it does not cause RISC-associated or microRNA-like off-target activity. Because GapmeRs are short (13-20 nucleotides), off-target and mismatches have rarely occurred 14,26,27 . In the present study, we have been using antisense LNA GapmeRs to knock down lncRNA MIR100HG in acute promyelocytic This article can be downloaded from www.ijlpr.com L-18 leukemia (AML-M3) cell line (HL60).…”
Section: Discussionmentioning
confidence: 99%